The Effect of Environmental, Social and Government Disclosure on Company Value With Company Size as a Moderation - Gabriella Shofiach Parinussa; Jefry Gasperz; Dwi Hariyanty (LP2M IAIN Palopo, 2025)
The effect of ESG disclosure on company value with company size as a moderator (supervised by Jefry Gaspersz and Dwi Haryanti) This research aims to determine the effect of ESG disclosure on company value with company size as a moderator in Non-Financial Companies on the Indonesia Stock Exchange, and to empirically test the effect of company size as a moderator of ESG disclosure on company value in Non-Financial companies on the Indonesia Stock Exchange in 2019-2023. The method used is descriptive quantitative using Eviews as a tool for testing. The research results show that the Environmental disclosure variable has a significant effect on company value, so it can be concluded that H1 is accepted. Social disclosure has a significant effect on company value. The governance disclosure variable does not have a significant effect on firm value. Company size has a significant effect in moderating the relationship between ESG disclosure and company value. Company size has a significant influence in moderating the relationship between social disclosure and company value. Company size is not able to moderate the relationship between governance and company value.